Answer:
[tex]x=\frac{h}{4}-3y-\frac{1}{2}[/tex]
Step-by-step explanation:
This equation has "h" as the subject. Now, making "x" the subject means to use algebra and re-arrange the equation so we have "x = SOMETHING".
First, we will use distributive property on the RHS of the equation. The distributive property is:
[tex]a(b+c)=ab+ac[/tex]
So, we have:
[tex]h=4(x+3y)+2\\h=4x+12y+2[/tex]
Since we want "x" as the subject, we put "x" term on one side and everything else on another and solve for x. Shown below:
[tex]h=4x+12y+2\\4x=h-12y-2\\x=\frac{h-12y-2}{4}\\x=\frac{h}{4}-3y-\frac{1}{2}[/tex]
This is the answer.